RESEARCH IN THE SERVICE OF CO‐LEARNING: SUSTAINABILITY AND COMMUNITY ENGAGEMENT - VanWynsberghe, Rob; Andruske, Cynthia (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
This research, conducted with an introductory sociology class at the University of British Columbia during the 2001‐2002 academic year, explored community service‐ learning as a pedagogy and philosophy. The theoretical focus of this paper is Nancy Fraser’s (1997) criticisms of Jurgen Habermas’ (1992) bourgeois liberal model of the public sphere. We analyzed the class experiences with community service that emerged from students’ contributions to a database of community organizations, concept maps, and a student‐driven course evaluation. The outcomes of this research include a description of potentially useful course strategies and a narrative of a unique type of community‐service learning. Key words: community‐service learning, public sphere, citzenship, learning Cette recherche menée dans le cadre d’un cours d’introduction à la sociologie à l’Université de Colombie‐Britannique au cours de l’année universitaire 2001‐2002 portait sur l’apprentissage par l’engagement communautaire en tant que pédagogie et philosophie. La théorie sous‐jacente à cet article est tirée des critiques de Nancy Fraser (1997) au sujet du modèle libéral bourgeois de la sphère publique de Jurgen Habermas (1992). Les auteurs ont analysé les expériences du service communautaire qu’ont pu vivre les étudiants à travers leurs contributions à une base de données d’organisations communautaires, à des cartes conceptuelles et à une évaluation du cours. Les résultats de cette recherche comprennent une description de stratégies pédagogiques potentiellement utiles et un récit portant sur un type unique d’apprentissage par l’engagement communautaire Mots clés: apprentissage par l’engagement communautaire, sphère publique, citoyenneté, apprentissage